2017
DOI: 10.1016/j.soard.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Risk of low birth weight and micronutrient deficiencies in neonates from mothers after gastric bypass: a case control study

Abstract: Background: An increased risk of small-for-gestational-age infants after maternal bariatric surgery has been shown. The risk of micronutrients deficiencies in these neonates is unclear. Objective: To screen for micronutrients deficiencies in newborns of mothers with gastric bypass. Settings: University hospital in Angers, France. Methods: This study compared the clinical and cord blood biological characteristics of 56 newborns of mothers with prior Roux-en-Y gastric bypass (RYGB) and 56 newborns of nonobese he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 35 publications
4
37
0
7
Order By: Relevance
“…While neonatal growth restriction after maternal GB surgery is a well described phenomenon [4,6], the underlying pathophysiol-ogy for these observation remains elusive. In a recent study on cord blood samples in neonates of gastric bypass patients, insulin and IGF-1 deviations, but no other micronutrient deficiencies were associated with growth restriction at birth [5]. This is comparable to studies on undernourished non-human primates, where caloric restriction was shown to affect fetal growth directly through placental inhibition of insulin and IGF-1 pathways, decreasing mTOR activity and resulting in downregulation of placental protein and glucose transporters.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…While neonatal growth restriction after maternal GB surgery is a well described phenomenon [4,6], the underlying pathophysiol-ogy for these observation remains elusive. In a recent study on cord blood samples in neonates of gastric bypass patients, insulin and IGF-1 deviations, but no other micronutrient deficiencies were associated with growth restriction at birth [5]. This is comparable to studies on undernourished non-human primates, where caloric restriction was shown to affect fetal growth directly through placental inhibition of insulin and IGF-1 pathways, decreasing mTOR activity and resulting in downregulation of placental protein and glucose transporters.…”
Section: Discussionsupporting
confidence: 64%
“…Likewise, distinct metabolic and neurologic long-term consequences of children born SGA have been described, such as impaired glucose tolerance [26], impaired cognitive scores in school age children, as well as reduced academic achievement and professional attainment in adulthood [27]. Even though micronutrient deficiencies in GB did not correlate with fetal growth restriction, they might impact long-term neurological and cognitive outcome [5]. Investigations on long-term effects of gastric bypass-related growth restriction on children's health and metabolism are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired serum retinol levels were also observed in neonates from mothers who underwent RYGB 11–69 months before the onset of pregnancy, which may cause irreversible eye problems in the child [ 99 ]. In contrast to retinol, circulating levels of vitamin D and E were higher in neonates of mothers who had undergone bariatric surgery as compared to neonates from healthy mothers [ 100 ]. This argues against a general deficiency in fat-soluble vitamins in these children.…”
Section: Vitamin a And Rbp4 In The Clinical Course Of Nafld And Mementioning
confidence: 99%
“…Vitamin B12 (B12) is an essential coenzyme important for fetal development. Maternal B12 deficiency during pregnancy has been associated with poor fetal outcomes such as intrauterine growth retardation, recurrent fetal loss, low birth weight, and neural tube defects [ 1 , 2 , 3 , 4 , 5 ]. Yet, a rare group of patients presents a paradox.…”
Section: Introductionmentioning
confidence: 99%